Predictive factors for neuromotor abnormalities at the corrected age of 12 months in very low birth weight premature infants Fatores preditivos para anormalidades neuromotoras aos 12 meses de idade corrigida em prematuros de muito baixo peso - Rosane Reis de Mello; Kátia Silveira da Silva; Maura Calixto Cecherelli de Rodrigues; Geórgia Chalfun; Rachel Carvalho Ferreira; Juliana Verçosa Rocha Delamônica (Arquivos de Neuro-Psiquiatria)
BACKGROUND: The increase in survival of premature newborns has sparked growing interest in the prediction of their long-term neurodevelopment. OBJECTIVE: To estimate the incidence of neuromotor abnormalities at the corrected age of 12 months and to identify the predictive factors associated with altered neuromotor development in very low birth weight premature infants. METHOD: Cohort study. The sample included 100 premature infants. The outcome was neuromotor development at 12 months classified by Bayley Scale (PDI) and neurological assessment (tonus, reflexes, posture). A multivariate logistic regression model was constructed. Neonatal variables and neuromotor abnormalities up to 6 months of corrected age were selected by bivariate analysis. RESULTS: Mean birth weight was 1126g (SD: 240). Abnormal neuromotor development was presented in 60 children at 12 months corrected age. CONCLUSION: According to the model, patients with a diagnosis including bronchopulmonary dysplasia, hypertonia of lower extremities, truncal hypotonia showed a 94.0% probability of neuromotor involvement at 12 months. INTRODUÇÃO: O aumento na sobrevida de recém-nascidos prematuros tem suscitado interesse crescente na predição do seu neurodesenvolvimento a longo prazo. OBJETIVO: Estimar a incidência de anormalidades neuromotoras aos 12 meses de idade corrigida e identificar os fatores associados ao desenvolvimento neuromotor alterado em prematuros de muito baixo peso. MÉTODO: Estudo de coorte. A amostra incluiu 100 crianças prematuras.O desfecho foi o desenvolvimento neuromotor aos 12 meses. Modelo de regressão logística multivariado foi construído. Variáveis neonatais e anormalidades neuromotoras até os 6 meses de idade corrigida foram selecionadas por análise bivariada. RESULTADOS: O peso de nascimento médio foi 1126g (DP:240). Aos 12 meses 60% das crianças apresentaram desenvolvimento neuromotor alterado. CONCLUSÃO: De acordo com o modelo, pacientes com diagnóstico incluindo displasia broncopulmonar, hipertonia de membros inferiores e hipotonia de tronco tinham 94% de probabilidade de comprometimento neuromotor aos 12 meses.